The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/2179-10742016v15i2558
|View full text |Cite
|
Sign up to set email alerts
|

Design of high gain and wide band EBG resonator antenna with dual layers of same dielectric superstrate at X-bands

Abstract: Abstract-A wide band EBG resonator antenna with two layer of dielectric superstrates of the same material is design which is operating in X band. The EBG superstrates act as Partially Reflective Surfaces (PRS) having positive reflection phase curve which are suspended above a double sided dipole patch antenna fed by a coaxial cable pass through ground plane. Thus a resonator cavity is constructed which increases the bandwidth and gain of the feed antenna. The measured results validate the simulation results ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It is concluded that the present work improves the bandwidth for approximately 1.6 GHz and the directivity for about 0.72 dB. Also, compared with previous works in the X-band [8,[35][36][37][38], the structure is smaller in size and more simple with fewer numbers of layers. As for the effects of metamaterial substrate on radiation pattern, previous works show some squint and deviation.…”
mentioning
confidence: 61%
“…It is concluded that the present work improves the bandwidth for approximately 1.6 GHz and the directivity for about 0.72 dB. Also, compared with previous works in the X-band [8,[35][36][37][38], the structure is smaller in size and more simple with fewer numbers of layers. As for the effects of metamaterial substrate on radiation pattern, previous works show some squint and deviation.…”
mentioning
confidence: 61%
“…The proposed antenna has a smaller volume than [2,[30][31][32][33]. Moreover, it has the highest impedance bandwidth and the simplest design fabrication.…”
Section: Antenna Fabrication and Comparison With Various X-band Antennasmentioning
confidence: 99%
“…Others have studied the combination of EBG with antennas for SAR reduction [8], radar cross section reduction [9] and their use as filter building block [10]. Therefore, some recent works recourse to the EBG structures, to obtain high gain and wide band [23] and also conceive a multi-band circular polarization antenna [24].…”
Section: Introductionmentioning
confidence: 99%